Analysis of Structure, Conduct, Performance (SCP) Robusta Coffee Commodities (Coffea Canephora): - Bidari Silmi; Arti Yoesdiarti; Himmatul Miftah; Sumantri (Universitas Djuanda, 2020)
Coffee commodity is one of the commodities that is the main target of the priority sub-agenda for agro-industry improvement. Indonesia is the fourth largest producer in the world and makes coffee one of the leading plantation commodities. Robusta coffee in Babakan Madang District is one of the coffees that has the potential to be developed because it is a specialty type of coffee that has a distinctive taste and has a wide-open market. However, inadequate marketing due to low prices at the farm level is one of the problems for Robusta coffee in Babakan Madang District. This study aims to analyze the structure, conduct, performance of Robusta coffee in Babakan Madang District, Bogor Regency. Data were analyzed qualitatively and quantitatively using the approach structure, conduct, performance (SCP). The result of this research is there are 6 established marketing channels, with channel II having the largest sales volume. Analysis of the market structure formed for the marketing of Robusta coffee is monopolistic competition at the farmer level. The level of village collector traders is oligopoly, large trader 1 and large trader 2 monopoly. The Robusta coffee market is very highly concentrated. Barriers to market entry are high for new competitors. In market behavior, the marketing functions performed by each marketing agency are exchange, physical, and facility functions. The price determination at the farm level is carried out by the marketing agency, then at the merchant level the price is determined by themselves. In market performance, the margin value and farmer's share efficient are obtained from channel VI, because on this channel the smallest margin value and they are obtained farmer share largest.